THE MARKET ORIENTATION AND PERFORMANCE RELATIONSHIP: THE EMPIRICAL LINK IN PRIVATE UNIVERSITIES - Sefnedi, Sefnedi (Jurnal Manajemen dan Kewirausahaan, 2017)
This study examines the empirical link between three dimensions of market orientation, namely, student orientation, competitor orientation and inter-functional coordination, and overall private university performance in Kopertis X. It was based on an empirical investigation of private universities located in Indonesia’s provinces of West Sumatera, Riau, Jambi, and Kepulauan Riau. The primary data for the study were collected from a self-administered mail survey of 237 questionnaires from the private university resulting in a sample of 114 usable responses being returned. From the application of the multiple regression analysis it was concluded that all three dimensions of market orientation had a significant impact on private university performance. Student orientation as a predictor variable is the strongest predictor of private university performance and followed by competitor orientation, and inter-functional coordination.